ETNOBOTANI TUMBUHAN OBAT DI MASYARAKAT ETNIS SIMALUNGUN KABUPATEN SIMALUNGUN PROVINSI SUMATERA UTARA - Helen Anjelina Simanjuntak (BIOLINK (Jurnal Biologi Lingkungan Industri Kesehatan), 2017)
Indonesia is a country with the second largest tropical forest in the world and has a high diversity of plants that is known as one of the seven megabio-diversity countries. Great biodiversity is stored potential of nutritious plants that can be utilized further. In addition to the diversity of these plants, Indonesia is also rich with ethnic and cultural diversity with a total of 1,068 ethnicities. Various Ethnic use of plants as ethnomedisin with the uniqueness of certain herbs and way of presentation. This study aims to inventoriate medicinal plants and parts used for herbs and inventory of medicinal herbs used by the people of Simalungun. This research uses explorative survey method with informant determination using purposive sampling from 5 subdistricts namely Silimakuta, Purba, Panei, Pematang Sidamanik and Dolok Batu Nanggar. The results show that healers / Battra are Simalungun. There are 92 Types of Medicinal Plants (TO) consisting of 28 Order and 45 Family. The highest percentage of families was found in Asteraceae and Euphorbiaceae with a value of 10.87%, the percentage of plant parts used was found in the leaf with a value of 55.21%, and the most widely used medicinal ingredients in treatment were for abdominal pain with a percentage of 9, 71%.